Effect of the structure of polymer inclusion membranes on zn(II) transport from chloride aqueous solutions. Issue 30 (2nd May 2015) - Baczyńska, Monika; Regel‐Rosocka, Magdalena; Nowicki, Marek; Wiśniewski, Maciej
ABSTRACT This article presents application of polymer inclusion membranes (PIM) containing polymer matrices: cellulose triacetate (CTA) or poly(vinyl) chloride (PVC), o‐nitrophenyloctyl ether (NPOE) as a plasticizer and phosphonium ionic liquids, i.e., trihexyltetradecylphosphonium chloride (Cyphos IL 101), bis(2, 4, 4‐trimethylpentyl)phosphinate (Cyphos IL 104) and tributyltetradecylphosphonium chloride (Cyphos IL 167), as carriers for Zn(II) transport from chloride medium. Cyphos IL167 application as an ion carrier in PIMs is reported for the first time. The membrane composition is found to affect Zn(II) transport significantly. SEM and AFM images show the differences in the surface morphology of PVC and CTA based membranes. Better transport abilities of CTA membranes (Zn(II) recovery factors exceed 80%) compared with those of PVC, indicate that the structural differences between the two polymers play a crucial role for the membrane permeability. The best initial flux and permeability coefficient are obtained for the membranes with Cyphos IL 101 and Cyphos IL 104 as carriers. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42319.